Innovation performance in digital economy: does digital platform capability, improvisation capability and organizational readiness really matter? - Jun, Wen; Nasir, Muhammad Hamid; Yousaf, Zahid; Khattak, Amira; Yasir, Muhammad; Javed, Asad; Shirazi, Syed Hamad (European journal of innovation management, 2022)
PurposeThe purpose of this study is to investigate how digital platforms capability, improvisational capability and organizational readiness directly affect innovation performance. This study also explores how organizational readiness acts as mediator.Design/methodology/approachThis empirical study is based on quantitative research design. Data were collected from 647 managers of small and medium enterprises (SMEs) working in Pakistan. Correlations and regression techniques were used for analyses. The Preacher and Hayes technique, the Sobel test and Bootstrap techniques were used to test mediation effect.FindingsThe results reveal a significant and positive relationship of digital platforms capability, improvisational capability and organizational readiness with innovation performance. Organizational readiness fully mediates the relationships between digital platforms capability and innovation performance link as well as between improvisational capability and innovation performance link.Originality/valueIn the age of digital economy the achievement of innovation performance is very important for SMEs. Businesses are shifting from traditional operational activities to digitalization. This study is imperative to offer new realm of modern technologies by exploring the role of digital platform capability, improvisational capability and organizational readiness for achieving innovation performance in digital economy.